THE EFFECT OF AMINO ACIDS AND VITAMIN D3 ON OBESE PATIENTS AND WEIGHT LOSS. LITERATURE REVIEW - Garnytska, Anna; Orlyk, Olga; Kochuieva, Maryna; Psarova, Valentyna (Eastern Ukrainian Medical Journal, 2025)
Obesity is a global problem in developed countries, which is becoming increasingly common not only among adults but also among children. The definition of obesity has changed significantly over the past century, from a simplistic view of overeating and laziness to a complex, multifactorial disease with profound consequences for health and society. Potential factors contributing to obesity include environmental, biological, genetic, and economic factors, as well as important influences on eating habits and behavior, the environment associated with food and beverages, and psychological and social factors acting inside and outside the body. The search for effective treatment strategies for this condition continues to this day. Among the auxiliary means of influencing carbohydrate metabolism, various micronutrients and vitamins are widely studied. Objective: Use literary sources to familiarize yourself with the properties of the amino acids arginine, leucine and vitamin D3, and their effect on carbohydrate metabolism and weight loss in obesity. Object: arginine, leucine and vitamin D3 as means of correction of carbohydrate metabolism disorders. Research methods: review of literature sources. Results: according to research and meta-analyses, certain amino acids, such as arginine and leucine, as well as vitamin D3, can affect metabolism and energy balance in the body. For example, leucine and arginine are amino acids that play an important role in the biochemical processes of the body. Their study in the context of obesity may include an analysis of the effect on metabolism, fat metabolism, insulin resistance and other parameters. In turn, vitamin D is a steroid hormone, the main function of which is the regulation of calcium and phosphorus metabolism. Still, this molecule also exhibits various properties, including the effect on carbohydrate metabolism. Conclusion: The integration of leucine, arginine and vitamin D3 into the diet may be one of the key strategies in the complex treatment of obesity